INSTITUTIONS, AGENTS AND PRACTICES OF IMMIGRATION CONTROL IN THE CONSOLIDATION OF SOCIETY: THE CASE OF FRANCE - A. G. Markaryan (Сравнительная политика, 2016)
Drawing on recent insight in citizenship regime literature, this article develops a macrotheoretical framework for understanding social and political tolerance of ethnic minorities. The paper attempts to analyze and describe the French experience of the role of institutions, agents and practices of immigration control in the consolidation of the society with the mechanisms for participatory democracy. It is shown that the question of the role and position of migrants in the host societies actualize the development of specific social policy constructing the image of migrants, the development of the legislative base, controlling migration flows, mechanisms of their adaptation and integration into the host society. It is concluded that as a result of the implementation of the migration policy, France prefers to rely on the discursive approach, the priority of human rights, rather than security considerations - dialectical contradiction and interaction that can be observed in the analysis of migration policies in the EU as a whole.